Evaluation of the Epidemiological Impact of Harm Reduction Programs on HIV in Vietnam - UNAIDS; World Bank (World Bank, Washington, DC, 2013)
Vietnam s HIV epidemic is concentrated, both in specific behavioral sub-populations and geographic regions. The key populations at higher risk for HIV infection in Vietnam are female sex workers (FSW) and their clients; injecting drug users (IDU); and men who have sex with men (MSM). Vietnam identified harm reduction interventions for IDU and FSW as a key component of its last 5-year National HIV strategy 2004-2009. Harm reduction interventions aim to reduce the dominant behavioral risk factors that facilitate transmission of HIV in Vietnam, namely, sharing injecting equipment and engaging in unprotected sex. The main service components of harm reduction for these groups include the distribution of free sterile needle-syringes and condoms and providing behavior change communication through peer educator-based outreach. As the next phase of programming is planned and resources allocated, it is important to assess the achievements of previous programs aimed at minimizing risk of infection in terms of coverage and epidemiological impact. This impact assessment study has the following objectives: To examine coverage of harm reduction interventions in Vietnam among IDU and FSW (programs targeted for MSM were not examined) from 2004-2009; to understand the HIV transmission dynamics in Vietnam and to estimate the extent to which harm reduction interventions among core groups have contributed towards epidemiological trends and reduced HIV transmission in Vietnam during the 2004-2009 strategy.